1H-Indole-3-carbaldehyde thiosemicarbazone - Rizal, R.M.; Ng, S.W.; Ali, Hapipah Mohd (International Union of Crystallography, 2008)
The molecules of the title compound, C10H10N4S, are linked by N-H-indole center dot center dot center dot S hydrogen bonds to form a linear hydrogenbonded chain. There are two independent molecules in the asymmetric unit.